Up‐regulation of pathogenesis‐related genes in strawberry leaves treated with powdery mildew‐suppressing ultraviolet irradiation. (28th April 2021) - Ota, Emi; Nishimura, Fumihiro; Mori, Mitsutaka; Tanaka, Masaya; Kanto, Takeshi; Hosokawa, Munetaka; Osakabe, Masahiro; Satou, Mamoru; Takeshita, Minoru
Abstract: Strawberry powdery mildew caused by Podosphaera aphanis, one of the most important diseases affecting strawberry production in Japan, can be effectively controlled by supplemental ultraviolet (UV) irradiation. Here, we investigated disease severity on plants irradiated with UV light at 270–380 nm with/without inoculation and demonstrated significant decreases in disease severity on the UV‐treated plants throughout almost all of the experiment periods. Daily UV irradiation for 3 hr (0.17–0.96 kJ ⋅m −2  ⋅day −1 ) significantly reduced the incidence of powdery mildew on UV‐treated strawberry at day 58 after initiation of UV irradiation in a natural infection and at day 168 in artificial inoculation tests compared with non‐UV‐treated controls. Furthermore, we found that two pathogenesis‐related protein (PR) genes were up‐regulated 7 days after initiation of UV irradiation on plants before or after transplantation into raised beds. Transcript levels of five defence‐response genes were estimated using quantitative reverse transcription PCR to determine whether UV irradiation induced a defence response; PR ‐ 3 and PR ‐ 5 transcripts were significantly higher in the UV‐treated strawberry leaves after UV irradiation than in the non‐irradiated controls. In addition, transcript levels of both genes were significantly up‐regulated in plants irradiated with a higher radiant dose (0.90–0.96 kJ ⋅m −2  ⋅day −1 ) within 7 days after initiation of UV treatment, compared with plants exposed to a lower dose (0.17 kJ ⋅m −2  ⋅day −1 ) and with controls. Thus, PR ‐ 3 and PR ‐ 5 are induced in strawberry leaves as part of a defence response that is induced by UV irradiation. Abstract : Ultraviolet irradiation, which significantly suppresses strawberry powdery mildew in greenhouses, can up‐regulate transcript levels of pathogenesis‐related genes in strawberry leaves.